The selection of beverage cafes using fuzzy TOPSIS / Wan Nurul Husna Wan Nordin, Nurafifah Md Zuhaimi and Rohani Muhamad - Wan Nordin, Wan Nurul Husna; Md Zuhaimi, Nurafifah; Muhamad, Rohani (Unit Penerbitan UiTM Kelantan, 2021)
Beverage Cafe business is growing too fast nowadays. Therefore, customers have many choices to choose the best cafe that suits their taste. The objectives of this study were to identify the most preferred beverage cafes by FSKM students and to evaluate the factors that influence their preferences using Fuzzy TOPSIS. This study also highlights five criteria for a cafe, namely price, taste, variety of menu, location, and service. The Fuzzy Technique for Order Performance by Similarity to Ideal Solution (FTOPSIS) was applied to solve a multicriteria decision-making (MCDM) problem. To rank all the alternatives, a similarity coefficient is calculated by calculating the distance to the fuzzy positive-ideal solution (FPIS) and fuzzy negative-ideal solution (FNIS) simultaneously. The higher the value of the closeness coefficient, the higher the ranking order of a particular beverage cafe that can satisfy consumer preferences.